RESOURCE CHARACTERISTICS OF THE PENAEID PRAWN PARAPENAEOPSIS STYLIFERA IN MANGALORE COAST - Ramamurthy, S (Indian Journal of Fisheries, 2011)
Some aspects of the populat’on characteristics of the prawn Parapenaeopsis stylifera from 1962 in the Mangalore coast are presented. The fishery experienced wide annual variations with two peaks in general, the primary one during April- May, the ancillary being during November-December. The maximum sustainable yield is oalculated to be 448 tonnes corresponding to an effort of approxdmately 32,000 boat days. The fishery was predominantly composed of size groups ranging from 73 to 93 mm and 83toll3 mmamong males and females respectively. Recruitment of smaller size groups was noticed mostly during Novembeir-December and’ iMarch-April. The maximum number of broods that could be noticed in a season w.’s six. Growth studies indicated that males and femaks attain a length of 90/95 and 110/125 mm at the end of one and two years respectively. In the case of males, the late 0-year class predominated whereas in irespect of females, either the late 0-year or one-year class was found to be predominsmt. The mean length showed considerable annual variations which appear to be due to natural causes. Females preponderated in fll the years except 1962-63. The average annual instantaneous rate of mortality for females between one and two year olds was estimated to be 4.28.